Gallstones due to hereditary spherocytosis with glucose-6-phosphate dehydrogenase deficiency - Kılınç, Yurdanur; Zorludemir, Ünal; Olcay, Işık (The Turkish Journal of Pediatrics, 1987)
A fourteen-year-old girl with hereditary spherocytosis and glucose-6-phosphate dehydrogenase deficiency is presented. She had pallor until eight years of age and experienced many icteric attacks until the day of admission. The intervals between the attacks became more frequent during the last year. Prior to her admission, abdominal pain developed and jaundice persisted because of gallstones. She was operated on and a gallbladder with stones and a spleen with two accessory spleens were removed. After the operation, the jaundice rapidly disappeared and improvement was observed in her blood and clinical picture.
Keywords: hereditary spherocytosis; glucose-6-phosphate dehydrogenase deficiency; gallstones